Influence of Design on the Performance and Perception of Inexperienced Users: A Comparison Between Forearm and Axillary Crutches - Almeida, Mariana Anjos de; Checoni, Milene de Almeida Ribeiro; Santos, Aline Darc Piculo dos; Medola, Fausto Orsi (DAT Journal, 2026)
Assistive walking devices (AWDs), such as axillary and forearm crutches, are essential for the mobility of individuals with motor impairments, and factors related to the user-device interaction influence the initial use experience. This study compared the functional performance and subjective perception of 20 healthy adults during their first use of axillary and forearm crutches. The Timed Up and Go (TUG) test and questionnaires addressing difficulty, discomfort, insecurity, and physical effort were administered. Both types of crutches increased completion time compared to independent walking, with forearm crutches showing greater variability in times and being rated as more difficult, less secure, and more physically demanding, while discomfort levels were similar to axillary crutches. The results underscore the importance of subjective perception and highlight design aspects of crutches that influence performance and perception during initial use.